2015
DOI: 10.1021/acs.chemmater.5b01362
|View full text |Cite
|
Sign up to set email alerts
|

Probing Reversible Multielectron Transfer and Structure Evolution of Li1.2Cr0.4Mn0.4O2 Cathode Material for Li-Ion Batteries in a Voltage Range of 1.0–4.8 V

Abstract: Li 1.2 Cr 0.4 Mn 0.4 O 2 (0.4LiCrO 2 ⋅0.4Li 2 MnO 3 ) is an interesting intercalation-type cathode material with high theoretical capacity of 387 mAh g -1 based on multiple-electron transfer of Cr 3+ /Cr 6+ . In this work, it has been demonstrated that the reversible Cr 3+ /Cr 6+ redox reaction can only be realized in a wide voltage range between 1.0 V and 4.8 V. This is mainly due to large polarization during the discharge. The reversible migration of the Cr ions between octahedral and tetrahedral sites leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 82 publications
(216 reference statements)
8
46
0
Order By: Relevance
“…Interestingly, the study of Li 1.2 Cr 0.4 Mn 0.4 O 2 shows that at high voltages, the Cr-K shift directly towards Cr 6+ with migration of Cr ions between octahedral and tetrahedral sites. 48 Inspired by the findings of the novel Cr 6+ behavior in our O-K XAS peak position map of Fig. 4 and these previous puzzling reports, we now investigate a series of Li 1.2 Cr 0.4 Mn 0.4 O 2 electrodes at different electrochemical states through both the Cr-L and O-K XAS, as shown in Fig.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Interestingly, the study of Li 1.2 Cr 0.4 Mn 0.4 O 2 shows that at high voltages, the Cr-K shift directly towards Cr 6+ with migration of Cr ions between octahedral and tetrahedral sites. 48 Inspired by the findings of the novel Cr 6+ behavior in our O-K XAS peak position map of Fig. 4 and these previous puzzling reports, we now investigate a series of Li 1.2 Cr 0.4 Mn 0.4 O 2 electrodes at different electrochemical states through both the Cr-L and O-K XAS, as shown in Fig.…”
mentioning
confidence: 76%
“…Although only reference V-based oxides are available for this study, electrodes based on Cr redox have been reported for Li-ion and Na-ion compounds. [47][48][49][50] The redox of Cr 4+/3+ was proposed in the previous works, however, the experimental evidences based on hard X-ray Cr-K edge XAS all show only small changes on the main K -edge lineshape upon charging, which is much different from the Cr 4+ reference spectrum. [47][48][49][50] Because TM K -edge main features correspond to 2s-4p excitations that are not the TM valence 3d states, the detection of the TM valence states through TM-K typically relies on the leading edge shift.…”
mentioning
confidence: 91%
“…The intensity of the peak for the FT EXAFS spectra is determined by two factors: the coordination number and the degree of disorder around the central atom. 42,43 The intensities of the Co-Co/Mn and Mn-Mn/Co peaks are reduced in the high voltage regions (a-d), which suggests significant local structural distortion (more disorder) upon oxidization of Co 3+ ions. During the discharging process (e-g), the intensities of both the Co-Co/Mn and Mn-Mn/Co peaks increase back to almost the original state, indicating that the structure is totally reverted.…”
Section: Characterization Electrochemical Behavior and Reaction Mecmentioning
confidence: 99%
“…Interestingly, the study of Li 1.2 Cr 0.4 Mn 0.4 O 2 shows that at high voltages, the Cr-K shift directly towards Cr 6+ with migration of Cr ions between octahedral and tetrahedral sites. 45 Inspired by the findings of the novel Cr 6+ behavior in our O-K XAS peak position map of Fig. 4 and these previous puzzling reports, we now investigate a series of Li 1.2 Cr 0.4 Mn 0.4 O 2 electrodes at different electrochemical states through both the Cr-L and O-K XAS, as shown in Fig.…”
Section: Low Highmentioning
confidence: 76%